PENERAPAN SANKSI YANG BERKEADILAN TERHADAP ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Wisnu Mulyadi, Aditya; Rai Djaja, Ida Bagus (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013, 2013)
To pass the sanction seems to be one of the most complicated things, which should be faced by a judge. To adjudicate a juvenile delinquency, especially how to give a just sanction, a judge should pass a sentence of several years jail or to give an educational punishment in the reformatory. This article talks about the applied sanction, which is just, toward juvenile delinquency. This is also based on the government law No. 11, 2012 dealing with the system of juvenile delinquency. Besides, this article explains the efforts done by a judge to investigate a juvenile delinquency based on the law by means of the approach of restorative justice and effort diversion.
Keywords: Applied Sanction, Juvenile Delinquency, Justification System of Juvenile Delinquency